Effectiveness of Records Management in Public Service Delivery: Evidence from a Secondary Data Review - Indah Sri Andini; Abdul Sahid; Ambo Masse (Journal of Indonesian Scholars for Social Research, 2026)
Effective records management is a core administrative capability because public services depend on the timely availability, authenticity, traceability, and security of information generated through government transactions. This study examines how records management contributes to public service effectiveness using secondary data only. An integrative document review was conducted using peer-reviewed studies, international standards, Indonesian legislation, and official archival policy documents. Sixteen substantive sources were purposively retained because they directly addressed records management, public-sector service delivery, accountability, transparency, or electronic records management. The material was coded thematically around service timeliness and retrieval, accuracy and evidentiary reliability, accountability and transparency, digital integration, and organizational capacity. The review shows that records management improves public service delivery primarily by reducing information-search delays, supporting consistent decisions, preserving evidence of administrative actions, strengthening access to information, and enabling continuity across organizational units. However, digitization alone does not guarantee effectiveness. Recurrent constraints include weak classification and retention controls, fragmented paper-digital workflows, limited professional capacity, inadequate infrastructure, weak management support, and incomplete compliance with archival rules. The Indonesian policy context provides a strong formal basis through Law No. 43 of 2009 on Archives, Law No. 25 of 2009 on Public Services, and the SRIKANDI integrated electronic records system, but implementation effectiveness depends on embedding records controls into day-to-day service processes. The study concludes that records management should be treated as service infrastructure rather than a back-office administrative function.